2020
DOI: 10.1002/jbmr.4186
|View full text |Cite
|
Sign up to set email alerts
|

Bone Tissue Composition in Postmenopausal Women Varies With Glycemic Control From Normal Glucose Tolerance to Type 2 Diabetes Mellitus

Abstract: The risk of fragility fracture increases for people with type 2 diabetes mellitus (T2DM), even after controlling for bone mineral density, body mass index, visual impairment, and falls. We hypothesize that progressive glycemic derangement alters microscale bone tissue composition. We used Fourier‐transform infrared (FTIR) imaging to analyze the composition of iliac crest biopsies from cohorts of postmenopausal women characterized by oral glucose tolerance testing: normal glucose tolerance (NGT; n = 35, age = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 74 publications
(99 reference statements)
2
19
1
Order By: Relevance
“…In fact, this mineral deposit was abnormal mineralization, possibly resulting in reduced bone absorption and bone strength. Hunt et al reported that mineral crystallinity was observed in patients with diabetes by FTIR (Hunt et al, 2021). This mineral crystallinity may be related to the mineral deposit found in this study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In fact, this mineral deposit was abnormal mineralization, possibly resulting in reduced bone absorption and bone strength. Hunt et al reported that mineral crystallinity was observed in patients with diabetes by FTIR (Hunt et al, 2021). This mineral crystallinity may be related to the mineral deposit found in this study.…”
Section: Discussionsupporting
confidence: 70%
“…The few studies on histological assessments of bone in DM have only included human samples obtained by biopsy or through autopsy. Recently, Hunt et al reported that worsening glycemic control was associated with greater mineral content and narrower distributions of acid phosphate using Fourier-transform infrared (FTIR) for the samples obtained by biopsy (Hunt et al, 2021). However, the actual histological mechanism of bone quality deterioration in DM is largely unknown (Jiang and Xia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Third, long-term hyperglycemia leads to the accumulation of advanced glycation end products (AGEs). Besides inhibiting the proliferation and differentiation of osteoblasts, AGEs accumulated in the body can not only promote oxidative stress and produce nonenzymatic crosslinking with type I collagen (the two best-characterized AGEs related to collagen are pentosidine and N-carboxymethyllysine) but also damage bone matrix and increase bone stiffness, increasing the chances of fractures (102,103). Although some studies indicated that serum or urinary levels of pentosidine correlated with the risk of vertebral fracture in T2DM (104, 105), the feasibility of predicting fracture risk needs to be further confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have studied the effects of elevated blood glucose in T2DM on advanced glycation end products (AGEs), mineral content and collagen. Elevated blood glucose in T2DM increases AGEs and mineral content [ 8 10 ]; hyperglycemia in T2DM leads to increased bone mineral content and average maturity of collagen [ 8 ]. Changes in bone microstructure and material properties (such as bone mineral and collagen) in patients with T2DM can lead to the decrease of bone quality and strength [ 6 ].…”
Section: Introductionmentioning
confidence: 99%